برصغیر پاک وہند میں تعامل بین المذاہب: وحدت ادیان اور پاکستان پر حالیہ استعماری اثرات: ایک جائزہ: Interfaith Interaction: Unity of Religions in the Subcontinent and Contemporary Colonialism effects on Pakistan - Asma Waseem; Dr. Muhammad Kalim Ullah Khan (Brunei) (Al Manhal Research Journal, 2024)
This research article discusses the concept of the unity of religions in the Indian subcontinent and the recent colonial influences on Pakistan. The discourse on the unity of religions has been present in the subcontinent from the beginning. There were attempts to portray Islam as a humanitarian religion similar to Hinduism, but these were internal matters of the subcontinent, with no external colonial involvement. However, with the arrival of the British, the discourse on religious interfaith dialogue took a new direction. In the 19th and 20th centuries, this issue gained significant importance. Even after the departure of colonial powers, their influence remained, and in Pakistan, it reached its peak under the guise of Sunat Ibrahimi. However, Islam does not accommodate the concept of the unity of religions. Instead, it advocates for the establishment of religion (Iqamat-e-Deen), where Islam is the only true religion. Islam promotes religious tolerance and considers and preaching as the foremost duties. It is also the responsibility of the Pakistani state to uphold these principles.